Die Hämophilie im morbiditätsorientierten Risikostrukturausgleich - Ballesteros, P. (Hämostaseologie, 2010)
Haemophilia presents a challenge to every risk adjustment scheme even if it uses diagnostical or pharmaceutical data. The German adjustment scheme developed by the Bundesversicherungsamt realizes fairly cost homogenous groups for many expensive diseases. It does not regard haemophilia. This holds true for the original classification system (grouper) from 2009 and for the improved classification procedure in 2010. The extreme peak costs that can originate from haemophilia cases can present a existential risk for small health plans.The chances to form cost-homogeneous subgroups of the haemophilia disease by more specific coding or other measures seem low because of the small number of cases affected by this disease. The complementary (re-)installation of a expenditure-oriented risk sharing is regarded as suited for improvement of the performance of the German risk adjustment scheme. This also corresponds to international experience and practice.
Keywords: German risk adjustment scheme; cost homogeneity; risk sharing